„Instrukcje obsługi kobiety i świata”. O (eko)poezji Julii Fiedorczuk - Grądziel-Wójcik, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Julia Fiedorczuk’s academic, journalistic and critical activity invites readings of her poetry in the context of ecopoetics, which she actively promotes. Her ecocritically oriented poems explore the links between poetry and natural environment, proposing an interdisciplinary practice of cocreation of the human and non-human world, as well as a re-evaluation of our understanding of the relations between them. It is, at the same time, a type of poetry that exposes its gender affiliation; it evokes and deconstructs the culturally instilled associations between femininity and nature, and formulates questions pertaining to identity and metaphysics. With her “woman and world: user’s manuals” project, poetically original yet deeply rooted in (post)modern contexts, Fiedorczuk represents one of the most interesting currents of contemporary – and not just women’s – poetry.